Suppression of Xanthomonas oryzae pv. oryzae biofilm formation by Acacia mangium methanol leaf extract - Shafiei,S. N. Sarah (2021)
Abstract Xanthomonas oryzae pv. oryzae (Xoo), a pathogen responsible for rice bacterial leaf blight, produces biofilm to protect viable Xoo cells from antimicrobial agents. A study was conducted to determine the potency of Acacia mangium methanol (AMMH) leaf extract as a Xoo biofilm inhibitor. Four concentrations (3.13, 6.25, 9.38, and 12.5 mg/mL) of AMMH leaf extract were tested for their ability to inhibit Xoo biofilm formation on a 96-well microtiter plate. The results showed that the negative controls had the highest O.D. values from other treatments, indicating the intense formation of biofilm. This was followed by the positive control (Streptomycin sulfate, 0.2 mg/mL) and AMMH leaf extract at concentration 3.13 mg/mL, which showed no significant differences in their O.D. values (1.96 and 1.57, respectively). All other treatments at concentrations of 6.25, 9.38, and 12.5 mg/mL showed no significant differences in their O.D. values (0.91, 0.79, and 0.53, respectively). For inhibition percentages, treatment with concentration 12.5 mg/mL gave the highest result (81.25%) followed by treatment at concentrations 6.25 and 9.38 mg/mL that showed no significant differences in their inhibition percentage (67.75% and 72.23%, respectively). Concentration 3.13 mg/mL resulted in 44.49% of biofilm inhibition and the positive control resulted in 30.75% of biofilm inhibition. Confocal laser scanning microscopy (CLSM) analysis of Xoo biofilm inhibition and breakdown showed the presence of non-viable Xoo cells and changes in aggregation size due to increase in AMMH leaf extract concentration. Control slides showed the absence of Xoo dead cells.